Austenitic stainless steel and hydrogen resistant member
The austenitic stainless steel with a tailored composition and controlled microstructure addresses the challenges of high strength, hydrogen embrittlement resistance, and processability in high-pressure hydrogen gas equipment, achieving efficient and cost-effective performance.
Patent Information
- Application Number
- JP2024118404
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-07-24
- Publication Date
- 2025-04-09
AI Technical Summary
Existing austenitic stainless steels used in high-pressure hydrogen gas equipment face challenges in achieving a balance between high strength, excellent hydrogen embrittlement resistance, and good processability, often requiring thick walls which increase device size and weight.
The development of an austenitic stainless steel with a specific composition that includes optimized levels of elements such as N, Si, B, and Co, along with a controlled number density of coarse alloy carbonitrides, to enhance strength, hydrogen embrittlement resistance, and processability.
The proposed austenitic stainless steel achieves high tensile strength of 690 MPa or more, excellent hydrogen embrittlement resistance, and improved processability, including enhanced cutting, cold workability, and weldability, while reducing the need for expensive elements like Ni.
Smart Images

Figure 2025058904000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an austenitic stainless steel and a hydrogen-resistant member, and more particularly to an austenitic stainless steel excellent in strength and hydrogen embrittlement resistance, and a hydrogen-resistant member using the same. [Background technology]
[0002] In recent years, the development of fuel cell vehicles that use hydrogen as fuel, and hydrogen stations that supply hydrogen to fuel cell vehicles, has been progressing. Various devices used in fuel cell vehicles and hydrogen stations (hereinafter collectively referred to as "high-pressure hydrogen gas equipment") are used in a high-pressure hydrogen gas environment, so the materials used in these devices are required to have excellent hydrogen embrittlement resistance. Stainless steel (especially austenitic stainless steel with an increased Ni equivalent) has excellent hydrogen embrittlement resistance and is suitable for this type of application.
[0003] Among austenitic stainless steels, SUS316L is known as a material with excellent hydrogen embrittlement resistance. Currently, SUS316L is certified as a stainless steel with excellent hydrogen embrittlement resistance in the standard for compressed hydrogen containers for automobiles set forth in the High Pressure Gas Safety Act. However, since SUS316L has low strength, it is necessary to design it to be thick when using it as a structural member for high-pressure hydrogen gas equipment. As a result, there is a problem that the equipment becomes unavoidably large and heavy. In order to reduce the weight of fuel cell vehicles, make hydrogen stations more compact, and realize high-pressure operation at hydrogen stations, it is preferable that the strength of the stainless steel used for these applications is high.
[0004] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 states: (a) containing predetermined amounts of C, Si, Mn, Cr, Ni, V, N, and Al, with the balance being Fe and impurities; (b) 2.5Cr+3.4Mn<300N Stainless steel for high pressure hydrogen gas is disclosed.
[0005] The same document states: (A) The most effective way to increase the strength of austenitic stainless steels is to use solid solution strengthening with N. As the amount of N added increases, strength improves, but ductility and toughness decrease; and (B) When the composition is adjusted so that 2.5Cr+3.4Mn<300N is satisfied, the tensile strength increases and the elongation also increases. is stated.
[0006] In Patent Document 2, (a) containing a predetermined amount of C, Si, Mn, Cr, Ni, Al, N, and at least one of V and Nb, with the balance being Fe and impurities; (b) the tensile strength is 800 MPa or more; (c) having a grain size number of 8 or more; (d) The content of alloy carbonitrides having a maximum diameter of 50 to 1000 nm is 0.4 pieces / μm 2 That's all. An austenitic stainless steel for high pressure hydrogen gas is disclosed.
[0007] The same document states: (A) The use of nitrogen as a solid solution element makes it possible to increase the strength of stainless steel, but the stacking fault energy is lowered, resulting in a decrease in durability against hydrogen environment embrittlement. (B) When V and / or Nb are added to steel, fine alloy carbides are precipitated during solution heat treatment, and the grains are refined by the pinning effect; and (C) Refining the grain size can improve the resistance of high-nitrogen steels to hydrogen environment embrittlement. is stated.
[0008] Patent Document 3 states: (a) containing predetermined amounts of C, Si, Mn, P, S, Ni, Cr, Mo, N, Nb, and V, with the balance being Fe and impurities; (b) 15≦12.6C+1.05Mn+Ni+15N is satisfied; (c) the grain size number is less than 8.0; (d) The tensile strength is 690 MPa or more. An austenitic stainless steel is disclosed.
[0009] The same document states: (A) When the grain size number is set to 8.0 or less, excellent machinability is obtained. (B) C, N, Mn, and Ni are all austenite stabilizing elements. When the contents of these elements are optimized, the austenite is stabilized, and even if the crystal grains are coarse, the hydrogen embrittlement resistance is increased; and (C) When 1.0% or more of Mo is added, high tensile strength can be obtained even if the grain size number is less than 8.0. is stated.
[0010] Furthermore, Patent Document 4 states: (a) containing predetermined amounts of C, Si, Mn, P, S, Ni, Cr, N, Mo, V, and Nb, with the balance being Fe and impurities; (b) the grain size number is 6.0 or more; (c) the tensile strength is 800 MPa or more; (d) The difference between the maximum and minimum tensile strength values is 50 MPa or less; (e) The number of alloy carbonitrides with a circle equivalent diameter exceeding 1000 nm is 10 / mm 2 That's all. (f) The difference between the maximum and minimum grain size numbers is 1.5 or less. An austenitic stainless steel material is disclosed.
[0011] The same document states: (A) When the grain size number is 6.0 or more and the difference between the maximum and minimum values of the grain size number (ΔGS) is 1.5 or less, the difference between the maximum and minimum values of the tensile strength is 50 MPa or less. (B) If the difference between the initial and final temperatures during hot working is 100°C or less, ΔGS can be suppressed to 1.5 or less; and (C) The grain size number is 6.0 or more, and the number of alloy carbonitrides exceeding 1000 nm is 10 / mm 2 If the temperature is increased to above 800MPa, a tensile strength of 800MPa or more can be obtained. is stated.
[0012] When materials with excellent hydrogen embrittlement resistance are used as structural members of high-pressure hydrogen gas equipment, the materials are often subjected to processing such as cutting, cold working, welding, etc. Therefore, this type of material is required not only to have excellent strength and hydrogen embrittlement resistance, but also to have excellent workability such as machinability, cold workability, and weldability. Furthermore, in order to reduce the manufacturing and maintenance costs of high-pressure hydrogen gas equipment, it is preferable that the materials used in such equipment can be used in their as-solution treated (solution heat treated) or as-welded state, and that they have a low content of expensive elements such as Ni.
[0013] Regarding these points, the stainless steel for high-pressure hydrogen gas described in Patent Document 1 has a strength of 700 MPa or more after solution treatment. However, since the stainless steel described in the same document has a high Mn content, excellent workability may not be obtained. The austenitic stainless steel for high-pressure hydrogen gas described in Patent Document 2 achieves fine grains and high strength by performing solution heat treatment, cold working, and secondary heat treatment. However, the cold working and secondary heat treatment increase the manufacturing cost.
[0014] Furthermore, the austenitic stainless steel described in Patent Document 3 is intended to be used in an as-hot worked state, and therefore the stainless steel described in the same document has an excessive amount of carbonitrides in the steel, resulting in poor workability. Similarly, the austenitic stainless steel described in Patent Document 4 is subjected to heat treatment after hot working at a low temperature (930°C to less than 1000°C), thereby precipitating a relatively large amount of relatively coarse alloy carbonitrides. Therefore, the stainless steel described in Patent Document 4 is also considered to have low workability. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] International Publication No. 2004 / 083477 [Patent Document 2] International Publication No. 2012 / 132992 [Patent Document 3] International Publication No. 2015 / 159554 [Patent Document 4] International Publication No. 2017 / 175739 Summary of the Invention [Problem to be solved by the invention]
[0016] An object of the present invention is to provide an austenitic stainless steel having excellent hydrogen embrittlement resistance, high strength, and further excellent workability. Another object of the present invention is to provide a hydrogen-resistant member using such an austenitic stainless steel. [Means for solving the problem]
[0017] The gist of the present invention for solving the above problems is as follows.
[0018] [1] Austenitic stainless steel with the following composition: (1) The austenitic stainless steel is C≦0.10mass%, Si≦0.50mass%, 3.0≦Mn≦8.0mass%, P≦0.30mass%, S≦0.30mass%, 7.0≦Ni≦12.0mass%, 18.0≦Cr≦28.0mass%, 1.0≦Mo≦3.0mass%, 0.03≦V≦0.50mass%, 0.0003≦B≦0.0300mass%, 0.0001≦Ca≦0.0300mass%, 0.35≦N≦0.80mass%, and 0.001≦Co≦1.00mass% The balance consists of Fe and unavoidable impurities. (2) The austenitic stainless steel has a number density of coarse alloy carbonitrides of 3×10 5 pieces / mm 2 The following is the result. Here, "coarse alloy carbonitrides" refers to alloy carbonitrides having an equivalent circle diameter of more than 1000 nm.
[0019] [2] W≦2.0mass%, Zr≦0.20mass%, and Ta≦0.50mass% The austenitic stainless steel according to [1], further comprising at least one selected from the group consisting of:
[0020] [3] An austenitic stainless steel according to [1] or [2], having a tensile strength measured at 25°C of 690 MPa or more.
[0021] [4] An austenitic stainless steel according to any one of [1] to [3], in which the grain size number of the austenite grains is less than 8.0.
[0022] [5] An austenitic stainless steel according to any of [1] to [4], having a fracture reduction of 30% or more measured at 25°C.
[0023] [6] A hydrogen-resistant component made of an austenitic stainless steel according to any one of [1] to [5].
[0024] [7] The hydrogen-resistant member according to [6], wherein the austenitic stainless steel includes a portion that is in an as-solution-treated state.
[0025] [8] A hydrogen-resistant member according to [6] or [7], having a butt weld, the as-welded tensile strength of the butt weld measured at 25°C being 690 MPa or more. Effect of the Invention
[0026] N is an austenite stabilizing element and a solid solution strengthening element, but it also reduces stacking fault energy. On the other hand, for example, Si is an element that reduces grain boundary strength, and B is an element that increases grain boundary strength. Therefore, by adding a relatively large amount of N to steel and optimizing the components (specifically, limiting the amount of elements that reduce grain boundary strength and adding an appropriate amount of elements that increase grain boundary strength), austenitic stainless steel with excellent hydrogen embrittlement resistance and high strength can be obtained. In addition, the amount of Ni contained in the steel can be reduced, so that the raw material cost can be reduced.
[0027] Furthermore, the austenitic stainless steel according to the present invention exhibits high strength even in the as-solution-treated or as-welded state. In addition, the amount of Mn is relatively small and the number density of coarse alloy carbides is small, so that the stainless steel has excellent workability. Furthermore, by optimizing the manufacturing conditions, the crystal grains become appropriately coarse, so that the workability is further improved. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a graph showing the relationship between the amount of Co and the relative reduction area (RRA) at −60° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] An embodiment of the present invention will be described in detail below. [1. Austenitic stainless steel] [1.1. Main constituent elements] The austenitic stainless steel according to the present invention contains the following elements, with the balance being Fe and unavoidable impurities. The types of added elements, their component ranges, and the reasons for their limitations are as follows:
[0030] (1) C≦0.10mass%: In the present invention, C is an impurity. If the C content is excessive, a large amount of carbides are precipitated, and the toughness, ductility, and corrosion resistance are reduced. Therefore, the C content must be 0.10 mass% or less. The C content is preferably less than 0.05 mass%, and more preferably 0.03 mass% or less. In the present invention, the smaller the C content, the better. However, an extreme reduction in the C content leads to an increase in manufacturing costs. In consideration of manufacturing costs, the C content is preferably 0.0005 mass% or more. The C content is more preferably 0.001 mass% or more.
[0031] (2)Si≦0.50mass%: In the present invention, Si is an impurity. Si combines with Ni and Cr to form intermetallic compounds. Si also promotes the growth of intermetallic compounds such as sigma phases. These intermetallic compounds reduce the hot workability of steel. Furthermore, if the Si content is excessive, the grain boundary strength decreases and the hydrogen embrittlement resistance decreases. Therefore, the Si content must be 0.50 mass% or less. The Si content is preferably 0.20 mass% or less, and more preferably 0.09 mass% or less. In the present invention, the smaller the Si content, the better. However, an extreme reduction in the Si content leads to an increase in manufacturing costs. In consideration of manufacturing costs, the Si content is preferably 0.001 mass% or more. The Si content is more preferably 0.01 mass% or more.
[0032] (3) 3.0≦Mn≦8.0mass%: Mn stabilizes austenite and suppresses the formation of martensite, which is highly susceptible to hydrogen embrittlement. Mn also increases the solubility of N in molten metal, contributing to improving strength. To obtain such effects, the Mn content must be 3.0 mass% or more. The Mn content is preferably 5.1 mass% or more, and more preferably 5.5 mass% or more. On the other hand, if the Mn content is excessive, the stacking fault energy and grain boundary strength decrease, and hydrogen embrittlement resistance decreases. Furthermore, if the Mn content is excessive, the toughness, ductility, and hot workability of the steel also decrease. Therefore, the Mn content must be 8.0 mass% or less. The Mn content is preferably 6.9 mass% or less, and more preferably 6.5 mass% or less.
[0033] (4)P≦0.30mass%: In the present invention, P is an impurity. If the P content is excessive, the hot workability and toughness / ductility of the steel are reduced. Furthermore, if the P content is excessive, the risk of solidification cracking during welding increases. Therefore, the P content must be 0.30 mass% or less. The P content is preferably less than 0.10 mass%, and more preferably 0.03 mass% or less. In the present invention, the smaller the P content, the better. However, an extreme reduction in the P content leads to an increase in manufacturing costs. In consideration of manufacturing costs, the P content is preferably 0.0005 mass% or more. The P content is more preferably 0.001 mass% or more.
[0034] (5)S≦0.30mass%: In the present invention, S is an impurity. If the S content is excessive, the toughness, ductility and hot workability of the steel are reduced. Furthermore, if the S content is excessive, the risk of cracking during welding increases. Therefore, the S content must be 0.30 mass% or less. The S content is preferably less than 0.10 mass%, and more preferably 0.09 mass% or less. In the present invention, the smaller the S content, the better. However, an extreme reduction in the S content leads to an increase in production costs. In consideration of production costs, the S content is preferably 0.0005 mass% or more. The S content is more preferably 0.001 mass% or more.
[0035] (6) 7.0≦Ni≦12.0mass%: Ni stabilizes austenite and increases stacking fault energy, thereby improving hydrogen embrittlement resistance. To obtain such effects, the Ni content must be 7.0 mass% or more. The Ni content is preferably 9.0 mass% or more, and more preferably 9.5 mass% or more. On the other hand, if the Ni content is excessive, the raw material cost increases. Also, if the Ni content is excessive, the solubility of N in the molten metal decreases, and the strength decreases. Therefore, the Ni content must be 12.0 mass% or less. The Ni content is preferably 10.5 mass% or less, and more preferably 9.9 mass% or less.
[0036] (7) 18.0≦Cr≦28.0mass%: Cr enhances the corrosion resistance of steel. Cr also increases the solubility of N in molten metal, contributing to improved strength. To obtain such effects, the Cr content must be 18.0 mass% or more. The Cr content is preferably 20.0 mass% or more, and more preferably 22.0 mass% or more. On the other hand, if the Cr content is excessive, intermetallic compounds and carbonitrides are likely to be excessively precipitated, and the toughness, ductility, and corrosion resistance of the steel are reduced. Therefore, the Cr content must be 28.0 mass% or less. The Cr content is preferably 26.0 mass% or less, and more preferably 25.0 mass% or less.
[0037] (8) 1.0≦Mo≦3.0mass%: Mo contributes to improving strength by solid solution strengthening austenite or forming carbonitrides. Mo also enhances the corrosion resistance of steel. To obtain such effects, the Mo content must be 1.0 mass% or more. The Mo content is preferably 1.5 mass% or more, and more preferably 1.8 mass% or more. On the other hand, if the Mo content is excessive, intermetallic compounds and carbonitrides are likely to be excessively precipitated, and the toughness and ductility of the steel are reduced. Furthermore, if the Mo content is excessive, the raw material cost also increases. Therefore, the Mo content must be 3.0 mass% or less. The Mo content is preferably 2.5 mass% or less, and more preferably 2.2 mass% or less.
[0038] (9) 0.03≦V≦0.50mass%: V forms hard alloy carbonitrides and improves the strength of steel. To obtain such an effect, the V content must be 0.03 mass% or more. The V content is preferably 0.05 mass% or more, and more preferably 0.08 mass% or more. On the other hand, if the V content is excessive, the alloy carbonitrides are excessively precipitated, and the toughness and ductility of the steel are reduced. Therefore, the V content must be 0.50 mass% or less. The V content is preferably 0.30 mass% or less, and more preferably 0.20 mass% or less.
[0039] (10) 0.0003≦B≦0.0300mass%: B segregates at grain boundaries to increase grain boundary adhesion and improve the strength of steel. B also suppresses embrittlement of steel in a hydrogen environment and improves hydrogen embrittlement resistance. Furthermore, B improves the hot workability of steel. To obtain such effects, the B content must be 0.0003 mass% or more. The B content is preferably 0.0005 mass% or more, and more preferably 0.0010 mass% or more. On the other hand, if the B content is excessive, the solidification cracking susceptibility of the molten metal increases when welding is performed without using a filler metal. Therefore, the B content must be 0.0300 mass% or less. The B content is preferably 0.0100 mass% or less, and more preferably 0.0050 mass% or less.
[0040] (11)0.0001≦Ca≦0.0300mass%: Ca improves the hot workability of steel. To obtain such an effect, the Ca content must be 0.0001 mass% or more. The Ca content is preferably 0.0003 mass% or more, and more preferably 0.0005 mass% or more. On the other hand, if the Ca content is excessive, Ca and O combine to reduce the cleanliness of the steel. As a result, the hot workability and toughness / ductility are also reduced. Therefore, the Ca content must be 0.0300 mass% or less. The Ca content is preferably 0.0150 mass% or less, and more preferably 0.0100 mass% or less.
[0041] (12) 0.35≦N≦0.80mass%: N stabilizes austenite and improves hydrogen embrittlement resistance. N also increases the strength of steel through solid solution strengthening and the formation of nitrides. Furthermore, N improves the corrosion resistance of steel. To obtain such effects, the N content must be 0.35 mass% or more. The N content is preferably 0.40 mass% or more, and more preferably 0.46 mass% or more.
[0042] On the other hand, if the N content is excessive, coarse nitrides are formed, and the toughness and ductility of the steel are reduced. Furthermore, if the N content is excessive, the hot workability of the steel is reduced, or blowholes (defects) are more likely to be formed during welding. Furthermore, if the N content is excessive, the stacking fault energy is reduced, and hydrogen embrittlement resistance is reduced. Therefore, the N content must be 0.80 mass% or less. The N content is preferably 0.60 mass% or less, and more preferably 0.53 mass% or less. In high nitrogen steel, a decrease in grain boundary strength can lead to a decrease in hydrogen embrittlement resistance. However, in the present invention, the grain boundary strength is improved by optimizing the Si content, B content, etc., and therefore the decrease in hydrogen embrittlement resistance can be suppressed.
[0043] (13) 0.001≦Co≦1.00mass%: Co is (a) The effect of stabilizing the austenitic structure and improving hydrogen embrittlement resistance; (b) Increases stacking fault energy and improves hydrogen embrittlement resistance. (c) The effect of increasing strength through solid solution strengthening. (d) improving toughness; and (e) Effect of suppressing deterioration of hydrogen embrittlement resistance after welding In order to obtain such an effect, the amount of Co must be 0.001 mass% or more. The amount of Co is preferably 0.07 mass% or more, 0.10 mass% or more, or 0.15 mass% or more. On the other hand, an excessive amount of Co leads to high costs, so the amount of Co is preferably 1.00 mass% or less.
[0044] [1.2. Sub-constituent elements] The austenitic stainless steel according to the present invention may further contain one or more of the following elements in addition to the above-mentioned main constituent elements. The types of the added elements, their component ranges, and the reasons for their limitations are as follows:
[0045] (1) W≦2.0 mass%: W has the effect of increasing corrosion resistance and the effect of increasing strength by forming a solid solution or carbonitride. Therefore, the austenitic stainless steel may further contain W. To obtain such effects, the W content is preferably 0.3 mass% or more. The W content is more preferably 0.8 mass% or more. On the other hand, if the amount of W is excessive, the raw material cost increases. Therefore, the amount of W is preferably 2.0 mass% or less. The amount of W is more preferably 1.5 mass% or less.
[0046] (2) Zr≦0.20mass%: Zr has the effect of forming crystallized oxides. The crystallized oxides become the starting points for the formation of inclusions such as MnS and carbonitrides, so the size of the inclusions can be reduced, improving toughness and ductility. Therefore, the austenitic stainless steel may further contain Zr instead of or in addition to W. To obtain such effects, the Zr content is preferably 0.01 mass% or more. The Zr content is more preferably 0.05 mass% or more. On the other hand, if the Zr content is excessive, coarse oxides are formed, which may reduce toughness and ductility. Therefore, the Zr content is preferably 0.20 mass% or less. The Zr content is more preferably 0.15 mass% or less.
[0047] (3)Ta≦0.50mass%: Ta has the effect of increasing strength by forming a solid solution or carbonitride. Therefore, the austenitic stainless steel may further contain Ta. The austenitic stainless steel may contain only Ta, or may further contain W and / or Zr in addition to Ta. To obtain such an effect, the Ta content is preferably more than 0.10 mass%. On the other hand, if the Ta content is excessive, the raw material cost increases, so the Ta content is preferably 0.50 mass% or less.
[0048] [1.3. Inevitable impurities] The inevitable impurities refer to elements that are mixed in from the ores and scraps used as raw materials for steel, or from the manufacturing process environment, etc. In addition to the above-mentioned C, Si, P, and S, the inevitable impurities include the following:
[0049] (1) Cu≦0.5mass%: In the present invention, Cu is an impurity. If the Cu content is excessive, there is an increased concern about solidification cracking during welding. Therefore, the Cu content is preferably 0.5 mass% or less. The Cu content is more preferably 0.4 mass% or less. In the present invention, the smaller the Cu content, the better. However, an extreme reduction in the Cu content leads to an increase in manufacturing costs. In consideration of manufacturing costs, the Cu content is preferably 0.005 mass% or more. The Cu content is more preferably 0.010 mass% or more.
[0050] (2) Al≦0.10 mass%: In the present invention, Al is an impurity. Al has the effect of deoxidizing steel, similar to Si. However, if the Al content is excessive, excessive nitrides are formed, and the toughness and ductility of the steel are reduced. Furthermore, if the Al content is excessive, the penetration depth during welding becomes shallow. Therefore, the Al content is preferably 0.10 mass% or less. The Al content is more preferably 0.05 mass% or less. In the present invention, the smaller the Al content, the better. However, an extreme reduction in the Al content leads to an increase in manufacturing costs. In consideration of manufacturing costs, the Al content is preferably 0.0005 mass% or more. The Al content is more preferably 0.001 mass% or more.
[0051] (3)O≦0.050mass% or less: In the present invention, O is an impurity. O reduces the hot workability of the base material during production. O also reduces the cleanliness of the steel and reduces the toughness and ductility of the steel. Therefore, the O content is preferably 0.050 mass% or less. The O content is more preferably 0.030 mass% or less, and even more preferably 0.010 mass% or less. In the present invention, the smaller the O content, the better. However, an extreme reduction in the O content leads to an increase in production costs. In consideration of production costs, the O content is preferably 0.0005 mass% or more. The O content is more preferably 0.001 mass% or more, and even more preferably 0.002 mass% or more.
[0052] (4) Other impurities: In addition to the above-mentioned components, the austenitic stainless steel according to the present invention may further contain the following components in the amounts shown below. In such cases, these components are treated as unavoidable impurities in the present invention. Nb<0.05mass%, Ta≦0.10mass%, Ti≦0.10mass%, Sn≦0.03mass%, Zn≦0.03mass%, Pd≦0.03mass%, Cd≦0.03mass%, Ag≦0.03mass%, Ga≦0.03mass%, As≦0.03mass%, La≦0.03mass%, Ce≦0.03mass%, Y≦0.03mass%, Sm≦0.03mass%, Se≦0.03mass%, Te≦0.03mass%, Bi≦0.03mass%, Pb≦0.03mass%, Mg≦0.03mass%, Sb≦0.03mass%, REM≦0.03mass%.
[0053] [1.4. Characteristics] [1.4.1. Number density of coarse alloy carbonitrides] "Coarse alloy carbonitrides" refers to alloy carbonitrides having an equivalent circle diameter of more than 1000 nm. The term "alloy carbonitride" refers to precipitates and inclusions containing carbonitride-forming elements such as Cr, V, Mo, W, Ta, Nb, and Ti as the main components, and which contain C or N, or both. Examples of alloy carbonitrides include: (a) CrN, (b) Z-phase (i.e., Cr(Nb,V)(C,N)), (c) MX type carbonitrides (M: Cr, V, Mo, Ta, Nb, Ti, etc., X: C, N) etc. "Number density of coarse alloy carbonitrides" refers to the number of coarse alloy carbonitrides per unit area (number / mm 2 The number density is determined by the following method.
[0054] That is, a sample including the center of a cross section perpendicular to the rolling or forging elongation direction of an austenitic stainless steel material is taken. The above observation area of the sample is mirror-polished. Then, in any 10 fields (200 μm × 200 μm) within the observation area, alloy carbonitrides are identified from among precipitates and inclusions in each field using a scanning electron microscope (SEM) equipped with an energy dispersive X-ray spectrometer (EDS). The circle-equivalent diameter of the alloy carbonitrides identified in each visual field is determined by image analysis. The circle-equivalent diameter means the diameter (nm) when the area of the alloy carbonitride in the visual field is converted into a circle. The number of alloy carbonitrides (coarse alloy carbonitrides) with a circle-equivalent diameter exceeding 1000 nm is counted. The average number of coarse alloy carbonitrides obtained in each of the 10 visual fields is defined as the "number density of coarse alloy carbonitrides (pieces / mm 2 )"
[0055] When excessive coarse alloy carbonitrides are precipitated in the matrix, the coarse alloy carbonitrides cause abrasive wear of tools, resulting in poor workability (machinability). On the other hand, by optimizing the composition of austenitic stainless steel and performing hot working and / or solution treatment under appropriate conditions, the number density of the coarse alloy carbonitrides can be reduced. To obtain excellent workability, the number density of the coarse alloy carbonitrides should be less than 3×10 5 pieces / mm 2 The number density is preferably less than 1×10 4 pieces / mm 2 More preferably, 1×10 3 pieces / mm 2 The following is the result. On the other hand, even coarse alloy carbonitrides contribute to tensile strength, so if you want to obtain austenitic stainless steel with higher strength, the number density should be less than 1 particle / mm 2 More preferably, 10 pieces / mm 2 That's all.
[0056] 1.4.2 Tensile strength "Tensile strength" refers to the tensile strength obtained by conducting a tensile test in accordance with JIS Z2241:2011 using a No. 14A test piece with a parallel section diameter of 6 mm. By optimizing the hot working conditions and / or solution treatment conditions, the austenitic stainless steel according to the present invention has a tensile strength of 690 MPa or more measured at 25° C. By further optimizing the components, the tensile strength can be increased to 750 MPa or more, or 800 MPa or more.
[0057] [1.4.3. Grain size number] The "grain size number" refers to a value measured in accordance with JIS G0551 (2005). Specifically, the grain size number is determined by the following method.
[0058] That is, a test piece for microscopic observation is taken from the austenitic stainless steel. The taken test piece is subjected to a microscopic test method for grain size specified in JIS G0551 (2005) to evaluate the grain size number. More specifically, the surface of the test piece is corroded with a known corroding solution (such as glycerol, Carling's reagent, or Marble's reagent) to reveal the grain boundaries on the surface. The grain size number of each of 10 visual fields on the corroded surface is determined. The area of each visual field is approximately 40 mm2. 2 The grain size number in each field is evaluated by comparing with the standard grain size chart specified in 7.1.2 of JIS G0551 (2005). The average of the grain size numbers in each field is defined as the grain size number of the austenitic stainless steel according to the present invention.
[0059] Since the austenitic stainless steel according to the present invention has optimized components, the grain size number of the austenite grains is less than 8.0 by optimizing the hot working conditions and / or the solution treatment conditions. If the grain size number is less than 8.0, the grains become appropriately large, and the cutting resistance is reduced. In addition, chips during cutting are easily removed from the workpiece and the cutting tool, and the chip disposability is improved. In other words, if the grain size number is less than 8.0, the machinability of the steel is improved. The grain size number is preferably 7.0 or less. On the other hand, if the grain size number is too low, the grains become excessively large, and the tensile strength of the steel may decrease. Therefore, the grain size number is preferably 2.0 or more. The grain size number is more preferably 3.0 or more.
[0060] [1.4.4. Breaking drawing] "Fracture reduction" is the ratio of the original cross-sectional area (S0) of the tensile test specimen before the test (S1) to the cross-sectional area (S2) of the tensile test specimen after the test (S3) in a tensile test conducted in accordance with JIS Z2241:2011 using a No. 14A test specimen with a parallel section diameter of 6 mm. u ) and the percentage of difference (=(S0-S u ) × 100 / S0).
[0061] In the austenitic stainless steel according to the present invention, the fracture reduction area measured at 25° C. is 30% or more by optimizing the hot working conditions and / or the solution treatment conditions. By further optimizing the components, the fracture reduction area is 40% or more, or 50% or more. In the present invention, the term "solution treatment" refers to a treatment in which a steel material is heated to 800° C. to 1200° C. for one minute or more, and then cooled by water cooling, oil cooling, air cooling, or at a cooling rate equivalent thereto.
[0062] [1.4.5. Hydrogen embrittlement resistance] The hydrogen embrittlement resistance can be evaluated by the magnitude of the relative reduction of area. Here, "relative reduction in area" refers to a value expressed by the following formula (1). The larger the value of the relative reduction in area expressed by formula (1), the better the hydrogen embrittlement resistance.
[0063] Relative aperture = A / B …(1) however, A is the fracture reduction of the round bar tensile test piece when a slow strain rate test was performed under the following conditions: test temperature: room temperature, test atmosphere: 87.5 MPa hydrogen gas, B is the fracture reduction of a round bar tensile test piece when a slow strain rate test was conducted under the following conditions: test temperature: room temperature, test atmosphere: 87.5 MPa helium gas. For the measurements of A and B, a round bar tensile test piece with a parallel part diameter of 4 mm was used, and the strain rate was 7×10 -5 / s.
[0064] In addition, it is known that the relative reduction of area, which is an index of hydrogen embrittlement resistance, is inferior in a slow strain rate test at low temperature compared to a slow strain rate test at room temperature. The austenitic stainless steel according to the present invention also exhibits excellent relative reduction of area in a slow strain rate test at low temperature. The relative reduction in area in a slow strain rate test at low temperature refers to the value expressed by the following formula (2). The larger the value of the relative reduction in area expressed by formula (2), the better the hydrogen embrittlement resistance.
[0065] Relative aperture = C / D … (2) C is the fracture reduction of the round bar tensile test piece when a slow strain rate test was performed under the following conditions: test temperature: -60°C, test atmosphere: 87.5 MPa hydrogen gas, D is the fracture reduction of a round bar tensile test piece when a slow strain rate test was conducted under the following conditions: test temperature: -60°C, test atmosphere: 87.5 MPa helium gas. For the measurements of C and D of the material before welding, round bar tensile test specimens with a parallel part diameter of 4 mm were used. On the other hand, for the measurements of C and D of the material after welding, plate tensile test specimens (parallel part width: 5 mm, parallel part thickness: 1.5 mm) were used. Furthermore, the strain rate was 7×10 -5 / s.
[0066] The austenitic stainless steel according to the present invention has excellent hydrogen embrittlement resistance because its components are optimized. When the components and structure of the austenitic stainless steel according to the present invention are optimized, the relative reduction of area becomes 0.8 or more. When the components and / or structure are further optimized, the relative reduction of area becomes 0.9 or more.
[0067] [1.5. Usage] The austenitic stainless steel according to the present invention has excellent resistance to hydrogen embrittlement, (a) As an austenitic stainless steel for high pressure hydrogen gas, or (b) As an austenitic stainless steel for liquid hydrogen environments It can be used.
[0068] In particular, the austenitic stainless steel according to the present invention has excellent toughness at cryogenic temperatures in addition to hydrogen embrittlement resistance, and is therefore suitable for use in, for example, (a) Liquid hydrogen pump booster type hydrogen station components, (b) Valve and pump components for liquid hydrogen It can be used as a material for liquid hydrogen environment components such as:
[0069] [2. Manufacturing methods for austenitic stainless steel] The austenitic stainless steel according to the present invention is (a) Melting and casting raw materials mixed to obtain a desired composition; (b) The resulting ingot is subjected to primary hot working. (c) The material obtained by the first hot processing is subjected to a second hot processing. (c) If necessary, perform cold working on the material after the secondary hot working. (d) If necessary, subject the secondary hot worked or cold worked material to a solution treatment; (e) If necessary, perform secondary hot working, cold working, or post-processing on the solution-treated material. This is obtained by:
[0070] [2.1. Melting and casting process] First, raw materials mixed to obtain a predetermined composition are melted and cast. The method and conditions for melting and casting are not particularly limited, and the most suitable method and conditions can be selected depending on the purpose. For example, an electric furnace, an AOD (Argon Oxygen Decarburization) furnace, a VOD (Vacuum Oxygen Decarburization) furnace, etc. can be used to produce molten steel. If necessary, the obtained ingot may be subjected to a homogenization heat treatment for removing segregation.
[0071] [2.2. Primary hot working process] Next, the obtained ingot is subjected to a primary hot working. The primary hot working is performed to destroy coarse cast structures, refine the structures, and at the same time, to convert the ingot into steel materials such as slabs, blooms, and billets. The primary hot working method is not particularly limited, and an optimal method can be selected depending on the purpose. Examples of the primary hot working method include hot forging and hot rolling. The produced molten steel may be used to directly produce steel materials such as slabs, blooms, and billets by continuous casting, in which case the first hot working step can be omitted.
[0072] [2.3. Secondary hot working process] Next, the material obtained in the first hot working step is subjected to a second hot working step. The second hot working step is performed to finish the material obtained in the first hot working step into a final product shape (e.g., steel plate, steel bar, wire rod, steel pipe, etc.) or a shape close to the final product shape. The method of the second hot working step is not particularly limited, and an optimal method can be selected depending on the purpose. Examples of the second hot working step include hot rolling, hot extrusion, and hot piercing rolling.
[0073] The conditions of the secondary hot working are not particularly limited, and the optimum conditions can be selected depending on the purpose. The secondary hot working may be performed multiple times depending on the purpose. If the heating temperature of the steel material before the secondary hot working is too low, the crystal grains may become excessively fine, and the machinability may decrease. Therefore, the heating temperature is preferably 900°C or higher. On the other hand, if the heating temperature is too high, there is a concern that local melting may occur, so the heating temperature is preferably 1300° C. or less.
[0074] In addition, when the secondary hot working is performed multiple times, the number density of the crystal grains and the coarse alloy carbonitrides can be optimized by optimizing the steel temperature at the end of the final secondary hot working. If the steel temperature is too low, the crystal grains may become too fine, and the machinability may decrease. Therefore, the steel temperature is preferably 800°C or higher. On the other hand, if the steel temperature becomes too high, there is a concern that local melting may occur, so the steel temperature is preferably 1200°C or less.
[0075] [2.4. Cold working process] Next, if necessary, the material after the secondary hot working may be subjected to cold working. The cold working method is not particularly limited, and an optimal method can be selected depending on the purpose. For example, when cold working the material into a steel pipe, it is preferable to use a cold drawing method. Alternatively, when processing the material into a steel plate, it is preferable to use a cold rolling method.
[0076] [2.5. Solution treatment process] Next, if necessary, the second hot worked or cold worked material may be subjected to a solution treatment. The solution treatment may be performed only once, or may be performed multiple times.
[0077] The solution treatment temperature affects the characteristics of the material. If the solution treatment is not performed or if the solution treatment temperature is too low, the number density of the coarse alloy carbonitrides becomes excessively high, and the reduction in area at break may decrease. In addition, the crystal grains may become excessively fine, and the machinability may decrease. Therefore, the solution treatment temperature is preferably 800°C or higher. The solution treatment temperature is more preferably 1000°C or higher. On the other hand, if the solution treatment temperature is too high, there is a concern that local melting may occur, and therefore the solution treatment temperature is preferably 1200°C or lower.
[0078] The holding time at the solution treatment temperature can be selected optimally depending on the purpose. In general, the longer the holding time of the solution treatment, the smaller the number density of the coarse alloy carbonitrides. On the other hand, if the holding time is longer than necessary, the crystal grains will become excessively coarse. The optimal holding time varies depending on the solution treatment temperature, but is usually 1 minute to 3 hours. After the holding time is completed, the material is cooled by water cooling, oil cooling, air cooling, or at a cooling rate equivalent to these.
[0079] [2.6. Post-processing process] If necessary, the material after the secondary hot working, cold working, or solution treatment may be subjected to further post-processing. Examples of post-processing include cutting, welding, and cold working. The members obtained in this manner are used for various purposes.
[0080] [3. Hydrogen-resistant materials] The hydrogen-resistant member according to the present invention is made of the austenitic stainless steel according to the present invention.
[0081] [3.1. Materials] The austenitic stainless steel according to the present invention has a specific composition and is therefore excellent in hydrogen embrittlement resistance. Other aspects of the composition of the austenitic stainless steel are as described above, and therefore will not be described here.
[0082] The austenitic stainless steel constituting the hydrogen-resistant member may be in any state, such as as hot worked, as cold worked, as solution treated, or after necessary post-working after solution treatment. In order to reduce the number density of coarse alloy carbonitrides and to reduce manufacturing costs, the austenitic stainless steel constituting the hydrogen-resistant member preferably contains a portion in the as solution treated state.
[0083] Here, "including a portion that is in the state of being solution-treated" means (a) The entire austenitic stainless steel constituting the hydrogen-resistant component is in the state in which it has been solution-treated, or (b) A portion of the austenitic stainless steel constituting the hydrogen-resistant component has been subjected to necessary post-processing (e.g., cutting, welding, etc.), but the other portions are in the state of being solution-treated. This refers to.
[0084] [3.2. Shape] The shape of the hydrogen-resistant member is not particularly limited, and an optimum shape can be selected depending on the purpose. The shape of the hydrogen-resistant member may be a tube, a rod, a wire, a plate, or the like. The hydrogen-resistant member may also be a member having a welded portion formed by welding together members having a predetermined shape. The type of seam of the welded portion (i.e., the welded joint) is not particularly limited, and an optimal welded joint can be selected depending on the purpose. Examples of welded joints include butt joints, T-joints, corner joints, lap joints, and edge joints.
[0085] When the hydrogen-resistant member includes a welded portion, the welding method is not particularly limited, and an optimal method can be selected according to the purpose. The welding method may be a welding method using a filler metal, or a welding method without a filler metal. Examples of the filler metal include YS316L, YS309LMo, YS308L, YS308H, YS308N2, and YS308LN. Welding methods using a filler metal include, for example, TIG welding, plasma welding, laser welding, MIG welding, MAG welding, and shielded metal arc welding. Welding methods that do not use a filler metal include, for example, TIG welding, plasma welding, and laser welding.
[0086] 3.3. Tensile strength of welds When the hydrogen-resistant member includes a welded portion, the member before welding is preferably solution-treated and has a tensile strength of 690 MPa or more measured at 25° C. The tensile strength is more preferably 750 MPa or more, and even more preferably 800 MPa or more. When welding is performed using a high-strength member, a high-strength hydrogen-resistant member is obtained.
[0087] Furthermore, by optimizing the composition and structure of the austenitic stainless steel, as well as the welding method and welding conditions, it is possible to obtain a hydrogen-resistant component that has high strength even in the as-welded state. For example, a hydrogen-resistant component including a butt weld can be obtained by using a TIG welding method without or with a filler metal and with a heat input of 0.20 to 0.60 kJ / mm. In this case, if the composition and structure of the austenitic stainless steel are optimized, a hydrogen-resistant component having a butt weld and a tensile strength of the butt weld as-welded, measured at 25°C, of 690 MPa or more can be obtained. If the composition and structure of the austenitic stainless steel are further optimized, the tensile strength of the weld can be 750 MPa or more, or 800 MPa or more.
[0088] Here, the "tensile strength of the butt weld" refers to the tensile strength when a tensile test is conducted in accordance with JIS Z3121:2013 using a No. 1A test piece having a parallel width of 12 mm and a plate thickness of 1.5 mm.
[0089] [4. Effect] N is an austenite stabilizing element and a solid solution strengthening element, but it also reduces stacking fault energy. On the other hand, for example, Si is an element that reduces grain boundary strength, and B is an element that increases grain boundary strength. Therefore, by adding a relatively large amount of N to steel and optimizing the components (specifically, limiting the amount of elements that reduce grain boundary strength and adding an appropriate amount of elements that increase grain boundary strength), austenitic stainless steel with excellent hydrogen embrittlement resistance and high strength can be obtained. In addition, the amount of Ni contained in the steel can be reduced, so that the raw material cost can be reduced.
[0090] Furthermore, the austenitic stainless steel according to the present invention exhibits high strength even in the as-solution-treated or as-welded state. In addition, the amount of Mn is relatively small and the number density of coarse alloy carbides is small, so that the stainless steel has excellent workability. Furthermore, by optimizing the manufacturing conditions, the crystal grains become appropriately coarse, so that the workability is further improved. EXAMPLES
[0091] (Examples 1 to 10, Comparative Examples 1 to 9) [1. Sample preparation] 50 kg of steel having the composition shown in Table 1 was melted in a vacuum induction furnace and cast into an ingot. The ingot was then subjected to hot forging, hot rolling, solution treatment, and machining to produce a steel bar having a diameter of 30 mm. In Table 1, the steels of Examples 5 to 7 have the same composition as the steel of Example 4, and the steel of Comparative Example 8 has the same composition as the steel of Comparative Example 7. Note that Example 7 and Comparative Example 7 were not subjected to solution treatment. Furthermore, the solution treatment temperature of Comparative Example 8 was 700°C. In the other cases, the solution treatment temperature was 900°C to 1100°C. In addition, two steel plates were prepared separately, and butt-welded by TIG welding without using a filler metal with a heat input of 0.20 to 0.60 kJ / mm.
[0092] [Table 1]
[0093] 2. Test Method [2.1. Grain size measurement] Each steel bar was cut parallel to the rolling direction. A sample for measuring grain size was taken from the cut surface, with the surface near the central axis of the steel bar as the observation surface. The observation surface of each sample was subjected to well-known electrolytic polishing. The grain size number of the observation surface after electrolytic polishing was determined based on the above-mentioned method.
[0094] [2.2. Measurement of the number density of coarse alloy carbonitrides] The number density of the coarse alloy carbonitrides was measured using the method described above.
[0095] [2.3. Evaluation of reduction in area and tensile strength] A round bar tensile test piece was taken from the center of each steel bar. The parallel part of the round bar tensile test piece was parallel to the rolling direction of the steel bar. The diameter of the parallel part was 6 mm. A tensile test was carried out using the round bar tensile test piece at room temperature (25°C) in air to determine the tensile strength TS (MPa).
[0096] Tensile tests were also conducted on each of the butt-welded components. Specifically, plate-shaped tensile test pieces were prepared from the butt-welded components, with the welded part located at the center of the parallel part. The width of the parallel part was 12 mm, and the thickness of the parallel part was 1.5 mm. Tensile tests were conducted on the plate-shaped tensile test pieces at room temperature to determine the tensile strength TS (MPa) of the butt welded part.
[0097] In the tensile tests using both the round bar tensile test piece and the plate tensile test piece, if the measured tensile strength TS (MPa) was 690 MPa or more, which is the required strength of the base material, it was marked as "○ (high strength)", and if it was less than 690 MPa, it was marked as "×". The reduction in area at fracture was calculated from the area of the fractured surface of the round bar tensile test piece after the tensile test. The reduction in area at fracture was 30% or more and was marked as "○ (large reduction in area at fracture)", and the reduction in area at fracture was less than 30% and marked as "×".
[0098] [2.4. Hydrogen embrittlement property evaluation] [2.4.1. No welding] To evaluate hydrogen compatibility, a slow strain rate test was carried out. The test temperature was room temperature or -60°C, and the test atmosphere was 87.5 MPa helium gas or hydrogen gas. Round bar tensile test specimens with a parallel part diameter of 4 mm were used as test specimens. The strain rate was 7×10 -5 / s. The fracture reduction in hydrogen gas and the fracture reduction in helium gas were calculated from the area of the fracture surface after the slow strain rate test of the round bar tensile test piece. Furthermore, using these, the relative reduction in area at room temperature (= A / B) and the relative reduction in area at -60°C (= C / D) were calculated. In each case, a relative reduction in area of 0.9 or more was rated as "◎ (particularly excellent hydrogen embrittlement resistance)", a relative reduction in area of 0.8 or more but less than 0.9 was rated as "○ (excellent hydrogen embrittlement resistance)", and a relative reduction in area of less than 0.80 was rated as "×". Incidentally, a -60°C high-pressure hydrogen gas environment is an environment in which the fracture reduction is most significantly reduced in austenitic stainless steels.
[0099] [2.4.2. With welding] A plate-shaped tensile test piece having a welded part at the center of the parallel part (width of parallel part: 5 mm, thickness of parallel part: 1.5 mm) was used as the test piece. In the same manner as in the "no welding" case, a slow strain rate test was conducted at -60°C, and the relative reduction in area (= C / D) at -60°C was calculated.
[0100] [2.5. Relative wear amount evaluation] A bar-shaped test specimen was taken from the center of each steel bar. The parallel part of the bar-shaped test specimen was parallel to the rolling direction of the steel bar. The cross section of the bar-shaped test specimen was circular and had a diameter of 8 mm.
[0101] A peeling process was carried out on the rod-shaped test piece for 5 minutes. The tool used for the peeling process was an uncoated carbide tool equivalent to JIS standard P20. The cutting speed was 100 m / min, the feed was 0.2 mm / rev, and the cutting depth was 1.0 mm. No lubricant was used during the peeling process. The peeling process was carried out under the above conditions, and the flank wear amount W1 (mm) of the carbide tool was measured after the test.
[0102] Furthermore, a bar-shaped test piece (hereinafter referred to as the "reference test piece") having a chemical composition equivalent to SUS316 of the JIS standard was prepared. The shape of the reference test piece was the same as that of the bar-shaped test piece. Using the reference test piece, peeling was performed under the same conditions as above, and the flank wear amount W0 (mm) of the cemented carbide tool after the test was measured. Based on the measurement results, the relative wear ratio defined by the following formula (3) was calculated. A relative wear ratio of 0.40 or more was evaluated as "○ (excellent machinability)", and a relative wear ratio of less than 0.40 was evaluated as "×". Relative wear ratio = W0 / W1…(3)
[0103] [3. Results] The results are shown in Table 2. The relationship between the Co amount and the relative reduction in area (RRA) at -60°C is shown in Figure 1. From Table 2 and Figure 1, the following can be seen. (1) The tensile strength is low in Comparative Examples 1 and 2. This is believed to be due to the low N content. (2) Comparative Example 3 has poor hydrogen embrittlement resistance. This is believed to be due to the excessive Si content. (3) Comparative Example 4 has poor hydrogen embrittlement resistance. This is believed to be due to the small amount of B.
[0104] (4) Comparative Example 5 has a high number density of coarse alloy carbonitrides and poor machinability. This is believed to be because the excessive Nb content increases the number density of coarse alloy carbonitrides, excessively promoting grain refinement, and promoting abrasive wear of the tool due to the coarse alloy carbides. (5) Comparative Example 6 has a high number density of coarse alloy carbonitrides and poor machinability. This is believed to be because the excessive Ti content increases the number density of coarse alloy carbonitrides, excessively promoting grain refinement, and promoting abrasive wear of the tool due to the coarse alloy carbonitrides.
[0105] (6) Comparative Example 7 has a high number density of coarse alloy carbonitrides and a large grain size number. This is believed to be due to the poor machinability. This is believed to be due to the low temperature at the end of the final secondary hot working. (8) Comparative Example 8 has a high number density of coarse alloy carbonitrides and a large grain size number. This is believed to be due to poor machinability. This is believed to be due to the low solution treatment temperature. (9) All of Examples 1 to 10 had a grain size number of less than 8 and were excellent in hydrogen embrittlement resistance. In addition, all of the tensile strengths were 690 MPa or more and the reduction in area at break was 30% or more. Furthermore, all of the relative wear ratios were 0.40 or more.
[0106] (10) The number density of coarse alloy carbides was smaller in Examples 1 to 4 than in Examples 5 to 7. This is believed to be due to the optimization of the hot working conditions and / or the solution treatment conditions. (11) Since Example 8 contains W, the tensile strength is improved compared to Examples 1 to 7. (12) Since Example 9 contains Zr, the reduction in area of fracture is improved compared to Examples 1 to 7. This is believed to be because inclusions such as MnS are made fine. (13) Example 10 had improved tensile strength compared to Examples 1 to 7 because it contained Ta.
[0107] (14) In the case of no welding, even when the Co content was less than 0.001 mass%, the RRA at -60°C exceeded 0.9. However, in the case of welding, when the Co content was less than 0.001 mass%, the RRA at -60°C was less than 0.8. See Comparative Example 9. (15) In the case of non-welded specimens, the RRA at -60°C gradually increased with an increase in the Co content. On the other hand, in the case of welded specimens, the RRA at -60°C increased sharply with an increase in the Co content. In particular, when the Co content was 0.15 mass% or more, the RRA at -60°C with welding became almost the same as that without welding. See Figure 1.
[0108] [Table 2]
[0109] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0110] The austenitic stainless steel according to the present invention can be used as a structural member for use in high-pressure hydrogen gas equipment.
Claims
1. Austenitic stainless steel with the following composition: (1) The austenitic stainless steel is C≦0.10mass%, Si≦0.50mass%, 3.0≦Mn≦8.0mass%, P≦0.30mass%, S≦0.30mass%, 7.0≦Ni≦12.0mass%, 18.0≦Cr≦28.0mass%, 1.0≦Mo≦3.0mass%, 0.03≦V≦0.50mass%, 0.0003≦B≦0.0300mass%, 0.0001≦Ca≦0.0300 mass%, 0.35≦N≦0.80 mass%, and 0.001≦Co≦1.00mass% and the balance being Fe and unavoidable impurities. (2) The austenitic stainless steel has a number density of coarse alloy carbonitrides of 3×10 5 pieces / mm 2 The following is the result. Here, "coarse alloy carbonitrides" refers to alloy carbonitrides having an equivalent circle diameter of more than 1000 nm.
2. W≦2.0mass%, Zr≦0.20 mass%, and Ta≦0.50mass% The austenitic stainless steel according to claim 1, further comprising at least one selected from the group consisting of:
3. 3. The austenitic stainless steel according to claim 1, having a tensile strength measured at 25° C. of 690 MPa or more.
4. 3. The austenitic stainless steel according to claim 1, wherein the grain size number of the austenitic grains is less than 8.
0.
5. 3. The austenitic stainless steel according to claim 1, wherein the fracture reduction area measured at 25° C. is 30% or more.
6. A hydrogen-resistant member made of the austenitic stainless steel according to claim 1 or 2.
7. 7. The hydrogen resistant member according to claim 6, wherein the austenitic stainless steel includes a portion that is in an as-solution-treated state.
8. 7. The hydrogen-resistant member according to claim 6, which has a butt weld, and the as-welded tensile strength of the butt weld measured at 25°C is 690 MPa or more.
Citation Information
Patent Citations
High-strength stainless steel, container and hardware made of such steel
WO2004083477A1
High-strength austenitic stainless steel for high-pressure hydrogen gas
WO2012132992A1
Austenitic stainless steel and method for producing same
WO2015159554A1
Austenitic stainless steel material
WO2017175739A1